2008
DOI: 10.1098/rsif.2008.0280
|View full text |Cite
|
Sign up to set email alerts
|

Maximal frustration as an immunological principle

Abstract: A fundamental problem in immunology is that of understanding how the immune system selects promptly which cells to kill without harming the body. This problem poses an apparent paradox. Strong reactivity against pathogens seems incompatible with perfect tolerance towards self. We propose a different view on cellular reactivity to overcome this paradox: effector functions should be seen as the outcome of cellular decisions which can be in conflict with other cells' decisions. We argue that if cellular systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Positive selection would homogenize the dynamics associating to all cells conjugation lifetime distributions with close normalization factors. This allows measuring conjugation lifetimes by measuring the rate of conjugations of a given duration [49] (see Fig 2a). …”
Section: Ordering and Detection In Cellular Frustrated Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Positive selection would homogenize the dynamics associating to all cells conjugation lifetime distributions with close normalization factors. This allows measuring conjugation lifetimes by measuring the rate of conjugations of a given duration [49] (see Fig 2a). …”
Section: Ordering and Detection In Cellular Frustrated Populationsmentioning
confidence: 99%
“…In [49] it was shown that conjugation lifetimes are inversely proportional to the probability of destabilizing a conjugate and consequently are related to how cells prioritize interactions. In a stationary regime it was derived that conjugation lifetimes τ ij can be calculated according to: …”
Section: Ordering and Detection In Cellular Frustrated Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular frustration framework (CFF) is a new approach capable of performing single intrusion detections in large populations of very diverse agents [1]. A classical approach in the literature consists in defining a set of detectors where each one surveys a sub-domain of the space of patterns that characterize non-self agents.…”
mentioning
confidence: 99%